The “Redemption” of Redemptive Societies - Ownby, David (Review of Religion and Chinese Society, 2019)
“Redemptive societies” is a term often used to refer to the organized expression of salvationist religious activity in Republican period China. These groups were a major part of Chinese social and cultural life in the decades preceding the Communist revolution, and are related, in ways that remain unclear, to the “White Lotus” sectarian traditions under the dynasties, and to the qigong boom of the 1980s and 1990s. This article assesses the state of the field of studies on redemptive societies, and offers suggestions for its future development.